Prediction of tennis ball landing location: a cognitive and ecological approach to visual perception - Thuot, S. M.; Garrett, G. E. (1999)
This study compared which approach (cognitive or ecological) best explained skilled tennis performers` ability to predict tennis ball landing location. The participants were 27 Division I male college tennis players, who observed two distinct video conditions representing the two divergent hypotheses. They viewed 24 video sequences of a live model executing four different strokes, and 24 video sequences of a tennis ball`s trajectory from a ball machine. Participants predicted the ball`s landing location by placing a dot on a paper diagram of a tennis court and circled their level of response confidence. Results showed that the ball machine condition was perceived AS closer than the live model condition. Live model left side shots were perceived right of the actual landing location, whereas right side shots were perceived more to the left. Conversely, ball machine left side shots were perceived left of actual landing location, and right shots more to the right. Depth ball machine responses were superior to live model, with the exception of the middle of the court, in which players severely underestimated the landing position of ball approaching head-on. Within the live model condition, traditional ground strokes were perceived more accurately than non-traditional ground strokes. Finally, response self-confidence was not related to successful response predictions. In summary, a limited ball flight trajectory was more informative than pre-contact visual cues. Thus, perceived emphasis is on information generated by the ball itself, not by the person propelling the ball.